• The Effect Of Brodifacoum On The Reproduction Of Male Wild House Mouse Mus musculus ( Muridae : Rodentia) - Mohammed, N. G; Kadhim, A.H.H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study dealt with the effect o r the anticoagu l ant rodentici de Brcidi facom on the reproduction of male mus musculus trapped from d i ftcrent loculitieo of Uagltdad prov ince and ted with different doses (50 ,75 ,100 mg) of pellets of this rodenticide. The results showed n significant decrease (p< 0.0 I ) in testicular weight and volume, epididymal ( head and tail) weight and numbers of different spermatogenic cells. The rodenticide caused a significant decrease in sperms concentration and a significant increase in dead and abnormal sperms in testes and epididymis.